Using a three-dimensional hydroxyapatite/graphene aerogel as a high-performance anode in microbial fuel cells. Issue 4 (August 2021) - Zhao, Ting; Qiu, Zhenghui; Zhang, Yu; Hu, Fangming; Zheng, Jiyong; Lin, Cunguo
Abstract: Bioaffinity of anode materials is a key factor for the power output of microbial fuel cells (MFCs). Anode surfaces with excellent biocompatibility can facilitate bacterial adhesion, biofilm propagation, and extracellular electron transfer. In this study, three-dimensional (3D) hydroxyapatite/graphene aerogel (HA/GA) was synthesized using a facile three-step method: hydrothermal treatment, dialysis, and freeze-drying. The HA/GA anode presented the excellent biocompatibility of HA and high conductivity of graphene. Moreover, the unique edge-to-edge cross-linked architecture of the HA/GA offered a large surface area for bacterial adhesion. Shewanella putrefaciens can generate more flavins through the introduction of highly biocompatible HA nanocrystals on the graphene sheets, leading to a rapid extracellular electron transfer between the biofilm and anode. An MFC containing a HA/GA anode delivered a maximum power density of 2.38 W m − 2, which was 1.83 times the power density achieved using a GA anode. Furthermore, MFCs equipped with HA/GA anodes were successfully utilized to drive a series of electrical appliances. The HA/GA anode possessed excellent biocompatibility, large surface area, superior hydrophilicity, and high conductivity, which were conducive for enhancing the surface bioaffinity and accelerating the interfacial charge transfer, thereby improving the electricity generation performance of the MFCs. This study has proven that HA is beneficial for enhancing the interface bioaffinity and that it can be applicable to MFC for high-performance bioelectricity harvesting. Graphical Abstract: The HA/GA anode with excellent biocompatibility, high conductivity and large surface area, which effectively enhancing the MFC's electricity generation. ga1 Highlights: A three-dimensional hydroxyapatite/graphene aerogel (HA/GA) as anode of microbial fuel cell. HA/GA exhibits high conductivity, large surface area and excellent biocompatibility. Hierarchical macroporous structure of HA/GA facilitates bacterial adhesion and substrate diffusion. HA could stimulate Shewanella putrefaciens to secrete riboflavin thus improving extracellular electron transfer efficiency. Th HA/GA anode can boost the power density of bioelectrochemical systems.